Preparation of Biodiesel from Hibiscus sabdariffa Seeds Oil using Calcium Oxide Catalyst from Waste Egg Shells - Hasni, K.; Nabi, A.; Varman, Mahendra; Ilham, Zul (Society of Automotive Engineers Malaysia, 2018)
The aim of this study is to optimize the transesterification process for conversion of Hibiscus sabdariffa seed oils (HSO) into biodiesel. Conversion of HSO into biodiesel were obtained at optimum parameters of methanol to oil ratio 6:1, temperature 67.5oC, 1% calcium oxide (CaO) catalyst derived from waste egg shells and agitation speed of 750 rpm. The yield achieved was 95.01%. The results showed that all of the fuel properties such as kinematic viscosity 4.55 mm2/s acid value 0.027 mg KOH/g, cloud point 3oC, pour point 1oC, flash point 161oC, cetane index 49 min and density 856 kg/m3 of the Hibiscus sabdariffa methyl esters (HSME), are in compliance within the range of ASTM D6751 and EN 14214 standard specifications except for oxidation stability which was at 3.48 hours. The results suggested that Hibiscus sabdariffa seed oil could be a potential feedstock for biodiesel.